Synergistic Inhibition of MRSA by Chenodeoxycholic Acid and Carbapenem Antibiotics - Kaiyu Cui; Weifeng Yang; Shuang Liu; Dongying Li; Lu Li; Xing Ren; Yanan Sun; Gaiying He; Shuhua Ma; Jidan Zhang; Qing Wei; Yi Wang (MDPI AG, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) has posed a severe global health threat. In this study, we screened an antibiotic and non-antibiotic combination that provides a viable strategy to solve this issue by broadening the antimicrobial spectrum. We found that chenodeoxycholic acid (CDCA) could synergistically act with carbapenem antibiotics to eradicate MRSA-related infections. This synergy specifically targets MRSA and was also validated using 25 clinical MRSA strains using time-kill analysis. We speculated that the underlying mechanism was associated with the interaction of penicillin-binding proteins (PBPs). As a result, the synergistic efficiency of CDCA with carbapenems targeting PBP1 was better than that of β-lactams targeting PBPs. Moreover, we showed that CDCA did not affect the expression level of PBPs, but sensitized MRSA to carbapenems by disrupting the cell membrane. In our study, we have revealed a novel synergistic combination of antibiotics and non-antibiotics to combat potential bacterial infections.